Antik davr manbalarida Makedoniyalik Aleksandr davlati - Qurbanazarova Sefogul Alisher qizi, Luqmonova Hilola Oʻtkir qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes the life, activities, and historical significance of Alexander the Great. Information is provided about his military campaigns, management style, and contribution to human culture.